ANALISIS EFISIENSI PEMASARAN KENTANG (Solanum tuberosum L.) DI KABUPATEN MAGETAN - Rekyani Puspitawati, Indah; Mustika Wardhani, Ratna (JURNAL AGRI-TEK, 2016)
Potatoes is one of the priority commodities for the domestic market resilience needs to be strangthened to reduce the pressure of imports. Potatoes are one of the horticultural crops consumed tuber. Increased production through intensification program requires an understanding of the problems of potato farmers. This understanding is not only limited to the cultivation techniques, but also includes the understanding of the problem the introduction of plants, uses, nutritional value and market potential. The role of marketing is quite large in the process of agricultural development. The purpose of this research was to determine the advantages of potato production in the district Plaosan Magetan regency based on the analysis of farming also to know the efficiency of potato marketed commodity marketing. This research uses analytical methods and their implementation with survey techniques. Method ot determinating the area of research using purposive sampling method in the district Plaosan (Puntukdoro village, Plaosan and Sarangan). Determination of the number of sample using snow ball sampling. The data used are primary data and secondary data. Data was collected with the recording, observation and interviews. Result of the analysis showed that the production of potato variety Granola farming more profitable than the varieties Atlantic. Marketing Granola potato varieties there are three marketing channels, channel I : farmers – market traders Plaosan – retailers – consumer, channel II : farmers – traders village collectors – market traders Plaosan – consumer, channel III : farmers – traders village collectors – market traders Plaosan – outside city traders – retailers – consumer. The most efficient marketing channel is channel I, with the lowest total margin is Rp 678,00 per kg and the share received by farmers are 87,39%.Keywords: Marketing Margin, Variety, marketing channels